Islamic Reform Relating to Conflict and Peace - Qamar-ul Huda (International Institute of Islamic Thought, 2007)
During 21-23 August 2006, sixteen Muslim scholars attended a three-day United States Institute of Peace (USIP) conference to discuss approaches to understanding conflict and peace in the Muslim world. Qamar-ul Huda (senior program officer, Religion and Peacemaking program) organized the conference, entitled “Islamic Reform Relating to Conflict and Peace.” Participants explored how scholars of Islamic studies can critically participate in Islamic peacebuilding and conflict resolution through an interdisciplinary analysis. The group discussed the challenges of peacebuilding in respect to asymmetric power, military institutions, non-democratic states, co-opted clergy, independent religious movements, authoritarian regimes, educational systems, media, the imbalance between classes, ethnic divides, postcolonialism, sectarianism, and other issues. Participants focused on how to advance nonviolent strategies for conflict mediation and peacebuilding within an Islamic cultural context. Asma Afsaruddin’s presentation on jihad, peace, martyrdom, patience, and the original Qur’anic context of these terms demonstrated the diversity of legal opinions in the Islamic tradition. According to her, not only did these different interpretations of violence, peace, and conflict resolution flourish, but there was also a culture of tolerating and fostering this pluralism. Only in the mid-tenth century did interpretations of peace, conflict, and just-war theories become driven by political expediency. With the emergence of competing dynasties and the rise of military expeditions, concepts of peace and conflict resolution became intertwined with the regime elites’ aspirations. The terms of the debate were appropriated by a political and military class that refused to countenance any challenge. Participants discussed the multiplicity of these interpretations and how violence is (and is not) legitimized. Mohammed Abu-Nimer discussed the theoretical and practical obstacles involved in changing views on conflict ...